Clinical Pattern and Malnutrition among Children with Congenital Heart Disease at Tertiary Care Hospital - Samar Gul, Fahad Nazir, Omair Mazhar, Qamar Uz Zaman, Zafar Iqbal Bhatti, Ahma Bilal, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Congenital heart disease is defined as the heart or intra-thoracic great vessel structural abnormalities present since birth with significantly functional irrespective of their detection age. It is the most prominent congenital anomaly and cause of morbidity and mortality among the pediatric age group population. The present study aimed to investigate the clinical pattern and malnutrition among children with congenital heart disease. Methodology: This descriptive cross-sectional study was carried out on 132 congenital heart disease patients in the Department of Pediatric, Imran Idrees Teaching Hospital Sialkot from January 2021 to December 2021. Children with clinical basis of cyanosis, feeding refusal, decreased activity, cough, hurried breathing, fever, and excessive sweating were enrolled. Acquired heart diseases and post-operative cardiac cases were excluded. Eligible children were assessed for sociodemographic details, physical examination, nutritional status, history, and types of congenital heart diseases. SPSS version 25 was used for data analysis. Results: Of the total 132 CHD children, there were 92 (69.7%) male and 40 (30.3%) females. The prevalence of acyanotic heart diseases, cyanotic heart diseases, complex CHD, and valvular diseases were 98 (74.2%), 22 (16.7%), 10 (7.6%), and 2 (1.5%) respectively. Age-wise distribution of all the children were as follows: 38 (28.8%) < 1 month, 62 (47%) 1 month-1 year, 20 (15.2%) 1-5 years, and 12 (9.1%) 5-10 years. Based on presented symptoms, the incidence of breathlessness, fever, cough, and other symptoms were 68 (51.5%), 58 (43.9%), 54 (40.9%), and 49 (37.1%) respectively. The incidence of protein-energy malnutrition and normal cases were 72 (54.5%) and 60 (45.5%) respectively. Anemia was the most prevalent risk factor CHD in 52 (39.4%) cases followed by pneumonia 41 (31.1%). Conclusion: The present study concluded that acyanotic heart diseases were the most commonly found in children followed by cyanotic, complex, and valvular diseases. Infancy and childhood age are more susceptible to congenital heart diseases. Breathlessness and fever were the most common symptoms. Nutritional anemia followed by pneumonia and failure to thrive were the major risk factors for congenital heart diseases among children. Keywords: Congenital heart diseases, Clinical pattern, Malnutrition